Can Ease of Doing Business Shorten the Distance and Attract Foreign Direct Investment - AL KHOORI, YOUSUF (2021)
Abstract Due to the accelerating pace of globalization, Multinational Enterprises (MNEs) have increasingly employed foreign direct investment (FDI) to enter foreign markets. FDI has played a key role in modernizing the economies of host countries and stimulating economic development. According to the United Nations Conference on Trade and Development (UNCTAD), FDI has grown worldwide from around $200 Billion in 1990 to $1.4 Trillion in 2019. This magnificent growth has sparked the interest of researchers to explain why multinational corporations prefer to operate overseas rather than exporting with arm’s length agreements? This thesis is based on the theoretical framework of the Dunning OLI Paradigm. The objective of this thesis is to expand on existing research by conducting a more fundamental and detailed analysis of the relationship between four different dimensions of distance (economic, geographic, institutional, and cultural) and foreign direct investment inflow. The scope of the thesis was broadened to include the possible existence of a moderating role of a favorable business environment, for which Ease of Doing Business Index (EODB) was used as a proxy, on the distance determinants and FDI inflow. Four country characteristics (including common border, common language, colonial ties, and free trade agreement) were added to the model as control measures. This research deployed the Structural Gravity Model to examine FDI flows into Singapore from its 30 largest investors for the period from 2006 to 2018. The empirical findings for testing the relationship between four different dimensions of distance and FDI largely confirmed expectations. However, the results of the moderating effect of a favorable business environment are novel and lead to additional insights for the determinants of FDI. Regarding the distance variables, with the exception of geographic distance (GeoDist), all are significant and exhibit their expected signs. The unexpected positive sign for the GeoDist dimension can be attributed to the combination of large FDI inflows from non-Asian countries combined with the close proximity of the Asian countries with Singapore. With regards to its moderating role, the ease of doing business (EODB) is effective in enhancing the positive influence of economic distance on FDI inflow. The empirical result also revealed that there is a significant moderating effect of doing business on the relationship between institutional distance and FDI inflows. In contrast to our theoretical assumptions, we found that the moderating effect of the ease of doing business index on the relationship between geographical distance and FDI is negatively significant. Interestingly, the result further indicates that the ease of doing business scoring does not moderate the relationship between cultural distance and FDI inflow. This research made significant theoretical and practical contributions within the field of FDI literature. The unifying theme of this thesis is the role that a business friendly environment plays as a moderator of the risks associated with four different measures of distance. From a theoretical viewpoint, a novel way to measure the degree to which a country exhibits a favorable business climate was created in order to weight the individual components of the World Bank’s Ease of Doing Business Index (EODB) according to their relative importance. Using this measure, our results show that a favorable business climate has a significant moderating effect on the risks that a MNC faces when investing in countries with significantly different wealth levels. In addition, this moderating effect is also evident for the risks associated with operating in countries with different legal and financial systems. Of equal importance for researchers is the contribution that a favorable business climate does not appear to exhibit a moderating effect for the risks associated with the cultural distance to the target country. In order to ensure that these results are reliable, a robust research design based on a structural gravity model using panel data of FDI flows was employed. From a practical viewpoint, this study provides strong evidence to policymakers that improving the business friendliness of a country attracts FDI due to the moderating effect that it has on the risks associated with economic distance and institutional distance.